Strategi Peningkatan Kemandirian Anak Usia Dini di TK. Dharma Wanita Brumbung 1 Kediri - Puspitasari, Dina Mei; Sa'diyah, Elok Halimatus (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2014)
The development of one's independence toward perfection becomes very important to be pursued since the early, more serious, systematic and programmed. As has been trying to do by the teacher in kindergarten. Dharma Wanita Brumbung I in order to increase the independence of children. Researchers interested in conducting research on the theme "Independence Strategy Increase Of Early Childhood In Kindergarten Dharma Wanita Brumbung I ".The research approach is qualitative. Techniques of data collection in this study is by interview, observation and documentation. Data analysis : data reduction, data presentation, drawing conclusions and verification of data. Subjects : 4 Women Brumbung I TK.Dharma teachers, where teachers who hold full responsibility for the child, while the child is in school.The results showed that strategy pursued in kindergarten teachers includes: provide positive self-understanding early childhood, which gives confidece and responsibility to the child.